Chronic Kidney Disease-Induced Arterial Media Calcification in Rats Prevented by Tissue Non-Specific Alkaline Phosphatase Substrate Supplementation Rather Than Inhibition of the Enzyme - Britt Opdebeeck; Ellen Neven; José Luis Millán; Anthony B. Pinkerton; Patrick C. D'Haese; Anja Verhulst (MDPI AG, 2021)
Patients with chronic kidney disease (CKD) suffer from arterial media calcification and a disturbed bone metabolism. Tissue-nonspecific alkaline phosphatase (TNAP) hydrolyzes the calcification inhibitor pyrophosphate (PPi) into inorganic phosphate (Pi) and thereby stimulates arterial media calcification as well as physiological bone mineralization. This study investigates whether the TNAP inhibitor SBI-425, PPi or the combination of both inhibit arterial media calcification in an 0.75% adenine rat model of CKD. Treatments started with the induction of CKD, including (i) rats with normal renal function (control diet) treated with vehicle and CKD rats treated with either (ii) vehicle, (iii) 10 mg/kg/day SBI-425, (iv) 120 µmol/kg/day PPi and (v) 120 µmol/kg/day PPi and 10 mg/kg/day SBI-425. All CKD groups developed a stable chronic renal failure reflected by hyperphosphatemia, hypocalcemia and high serum creatinine levels. CKD induced arterial media calcification and bone metabolic defects. All treatments, except for SBI-425 alone, blocked CKD-related arterial media calcification. More important, SBI-425 alone and in combination with PPi increased osteoid area pointing to a less efficient bone mineralization. Clearly, potential side effects on bone mineralization will need to be assessed in any clinical trial aimed at modifying the Pi/PPi ratio in CKD patients who already suffer from a compromised bone status.